Coordinate Control of Host Centrosome Position, Organelle Distribution, and Migratory Response by Toxoplasma gondii via Host mTORC2 - Wang, Yubao (American Society for Biochemistry and Molecular Biology, 2010)
The invasion of host cells by Toxoplasma gondii is accompanied by a reorganization of host cell structure, in which the host centrosome and Golgi apparatus are localized to the vacuole, and mitochondria, microtubules, and endolysosomes are recruited to the vacuole perimeter. The mechanism and functional significance of this process have not been well defined. Here, we report that the centrosome-vacuole association was abolished in mammalian target of rapamycin complex 2 (mTORC2)-deficient cells, which also displayed a disordered distribution of perivacuolar host mitochondria and lysosomes. Infection of fibroblasts led to stable, mTORC2-dependent activation of Akt, and Akt inhibition mimicked the effect of mTORC2 ablation on centrosome, mitochondria, and lysosome localization. Mobilization of the centrosome by Akt inhibition was abrogated by inhibitors of glycogen synthase kinase 3 (GSK3), implying that the centrosome is constrained to the vacuole through an mTORC2-Akt-GSK3 pathway. Infected cells were incapable of migration in a wounded monolayer model, and this effect was associated with the inability of centrosomes to reorient in the direction of migration. Both migration and centrosome reorientation were fully restored upon ablation of mTORC2. These findings provide the first linkage of host signals to parasite-mediated host cell reorganization and demonstrate migratory suppression as a novel functional consequence of this process that is associated with mTORC2-mediated centrosome constraint.